2018
DOI: 10.1186/s12954-018-0229-7
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use in Greece: an analysis of a representative population sample in Attica prefecture

Abstract: BackgroundThe purpose was to assess prevalence and correlates of electronic cigarette (e-cigarette) use in Greece in 2017.MethodsA cross-sectional survey of a representative sample of 4058 adults living in Attica prefecture (35% of the Greek adult population) was performed in May 2017 through telephone interviews. Prevalence and frequency of e-cigarette use were assessed according to the smoking status, and logistic regression analysis was performed to identify correlates of use.ResultsCurrent smoking was repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to examine the characteristics of vapers in India. Participants were mostly smokers and SLT users, in agreement with other studies of adult populations showing that ecigarette use is predominantly observed among current or former smokers [22,26,27]. The main results of this survey indicate that e-cigarettes could potentially be an effective partial or complete substitute for tobacco use for some smokers and SLT users in India.…”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, this is the first study to examine the characteristics of vapers in India. Participants were mostly smokers and SLT users, in agreement with other studies of adult populations showing that ecigarette use is predominantly observed among current or former smokers [22,26,27]. The main results of this survey indicate that e-cigarettes could potentially be an effective partial or complete substitute for tobacco use for some smokers and SLT users in India.…”
Section: Discussionsupporting
confidence: 88%
“…Adult vaping prevalence in selected western countries. Australia , Germany , Sweden , Finland , European Union , Canada , United States , France , New Zealand , Greece and Great Britain .…”
Section: Is There Enough Vaping To Influence Population Smoking Rates?mentioning
confidence: 99%
“…In the UK, an estimated 2.9 m smokers have quit smoking using e-cigarettes (Action on Smoking and Health ( ASH, 2017 )) and smoking cessation is the most commonly cited reason for use ( Office for National Statistics, 2016 ). E-cigarettes, therefore, have potential to aid smoking cessation and reduce smoking related disease and evidence suggests they are as, or more, effective than NRT ( Brown, Beard, Kotz, Michie, & West, 2014 ; McRobbie, Bullen, Hartmann-Boyce, & Hajek, 2012 ), though there is evidence from England and other EU countries that many smokers who use e-cigarettes also continue to smoke ( West, Beard, & Brown's, 2018 , Smoking Toolkit Study (STS); Farsalinos et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%